The Implications of Library Service Development on Students’ Satisfaction at the State Islamic University in Indonesia - Mukhtaruddin, Mukhtaruddin; Syukrinur, Syukrinur; Idris, Saifullah; Masrizal, Masrizal; Sulaiman, Sulaiman (Jurnal Ilmiah Peuradeun, 2022)
This research focused on (1) the development of library services at the State Islamic University (hereafter UIN) in Indonesia, and (2) the implications of library services for students’ learning satisfaction at UIN in Indonesia. This research used mix-methods using a purposive sampling technique. The samples were three library directors, 12 librarians, and 345 students. Data collections involved interviews, observations, and questionnaires, while the data were analyzed using a descriptive approach. The results showed that UIN in Indonesia developed the library services through planning, developing facilities, improving librarian competencies, enhancing the collaboration or network between libraries, and developing the library services. The results also revealed that the quality of library services at UIN in Indonesia was categorized as good, with an average of 76.62%. In contrast, the level of student satisfaction concerning the library services of UIN was classified as satisfactory, with an average of 76.91%. The library services had a strong implication on UIN students’ satisfaction, with a correlation coefficient of 0.765. This means that library services have a strong relationship with UIN students’ learning satisfaction in Indonesia.